2019
DOI: 10.1177/0300060519894801
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytocompatibility and osteogenic potential of calcium silicate-based dental cements in a root canal-filling model

Abstract: Objective To investigate the in vitro cytocompatibility and osteogenic potential of an experimental calcium silicate-based cement and the inflammatory response in human periodontal ligament stem cells (hPDLSCs). Methods Cellular responses, osteogenic-related gene expression, and the production of inflammatory cytokines including interleukin (IL)-6 and IL-8 were studied in hPDLSCs exposed to the experimental root canal-filling material C-Root, the commercial tricalcium silicate-based material BioRoot RCS, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Amongst the studies included in the present review, the in vitro assessment of the biomineralization exhibited by hPDLSCs cultured with CSCs or CSSs was performed by Alizarin Red S staining. In general terms, those biomaterials which produced positive results in cytocompatibility assays also produced positive results in the biomineralization assays (Jing et al, 2020;López-García et al, 2019Rodríguez-Lozano et al, 2020a,b;Sanz et al, 2020c), as shown in Tables 2 and 4.…”
Section: On the Results Of Studies: Cytocompatibility Differentiation And Mineralization Potential Of The Tested Materialsmentioning
confidence: 90%
See 4 more Smart Citations
“…Amongst the studies included in the present review, the in vitro assessment of the biomineralization exhibited by hPDLSCs cultured with CSCs or CSSs was performed by Alizarin Red S staining. In general terms, those biomaterials which produced positive results in cytocompatibility assays also produced positive results in the biomineralization assays (Jing et al, 2020;López-García et al, 2019Rodríguez-Lozano et al, 2020a,b;Sanz et al, 2020c), as shown in Tables 2 and 4.…”
Section: On the Results Of Studies: Cytocompatibility Differentiation And Mineralization Potential Of The Tested Materialsmentioning
confidence: 90%
“…In a similar manner, ES MTA showed negative results in MTT and wound healing assays using unconditioned hP-DLSC culture media as a reference (Collado-González et al, 2017a;López-García et al, 2020), and mixed results in SEM adhesion and morphology assays (positive (Lee et al, 2019) and negative (Collado-González et al, 2017a;López-García et al, 2020)). BR, however, exhibited significant mixed results in cytocompatibility assays (positive (Gaudin et al, 2020) and negative (Jing et al, 2020)), and significant positive results in migration, differentiation and mineralization assays (Gaudin et al, 2020). Additionally, BR exhibited a substantial hPDLSC spreading and attachment under SEM (Collado-González et al, 2017a).…”
Section: Study Resultsmentioning
confidence: 93%
See 3 more Smart Citations